A new 'rauisuchian' archosaur from the Middle Triassic Omingonde Formation (Karoo Supergroup) of Namibia. (18th April 2021) - Tolchard, Frederick; Smith, Roger M. H.; Arcucci, Andrea; Mocke, Helke; Choiniere, Jonah N.
Abstract : The Middle Triassic uppermost Omingonde Formation of Namibia records a fossil tetrapod fauna including stahleckeriid dicynodonts and probainognathian and traversodontid cynodonts, similar to other contemporary Gondwanan deposits. GSN F382 is a large predatory 'rauisuchian' archosaur from the uppermost Omingonde Formation that was originally identified as an erythrosuchid archosauriform. In this study, we provide a detailed anatomical description and phylogenetic analysis of the specimen and diagnose it as a new taxon, Etjosuchus recurvidens . Etjosuchus is a non-crocodylomorph loricatan, branching earlier than Rauisuchidae and Crocodylomorpha. The addition of this large-bodied carnivorous pseudosuchian archosaur to the uppermost Omingonde tetrapod assemblage reinforces its faunal similarity to other Middle to Late Triassic Gondwanan ecosystems such as those in the Santa Maria Formation of Brazil, the Chañares Formation of Argentina and the Manda Beds of Tanzania. http://zoobank.org/urn:lsid:zoobank.org:pub:F5035597-24E0-4DA5-B89D-D3CF8851A8FF